Effect of ozone on anthracnose physicochemical responses and gene expression in papaya (carica papaya l.) - Ong, Mei Kying (2014)
A study was conducted to investigate the effects of varying levels of ozone (0, 1.5, 2.5, 3.5 or 5.0 ppm) for 96 h on 1. the in vitro and in vivo growth of Colletotrichum gloeosporioides, the causal organism of anthracnose; 2. the reactive oxygen species generation and spore mitochondria of C. gloeosporioides using transmission electron microscope, fluorescence microscope and laser scanning confocal microscope; 3. the production of defence-related enzymes in papaya; 4. microbiological analysis on ozone-treated and non-treated papaya; 5. the biochemical, physiological, gas exchange and sensory characteristics of papaya fruit during storage (25 ± 3 °C, 70 ± 5 %RH) for 14 days; 6. the changes in total phenols, total carotenoids and antioxidant activity; and 7. gene expression of ozone-fumigated papaya fruit. Data were analyzed using analysis of variance and differences among treatment means were separated by Duncan Multiple Range Test (DMRT). The results of antifungal studies showed that mycelial growth of C. gloeosporioides was reduced significantly (p < 0.05) at all concentrations compared to the control. The maximum inhibition in mycelium growth (41.2 %) was obtained at 5.0 ppm ozone. Similarly, conidial germination inhibition was 100 % for 5 ppm ozone. In vivo analysis revealed that 2.5 ppm ozone was the optimal concentration for controlling anthracnose disease incidence (72.5 %) and disease severity after 10 days of storage, showing that a moderate concentration of ozone is effective in the reduction of C. gloeosporioides in artificially inoculated papaya fruit without affecting the quality aspect of the fruit. The results of scanning electron microscopy (SEM) also confirmed that ozone fumigated fungus at levels above 3.5 ppm deformed and disintegrated spore and mycelia structure. Further to that, transmission electron microscopy (TEM) illustrated that the mitochondria of ozonized fungus was disintegrated and had ruptured membrane. In spores treated with 3.5 ppm ozone, mitochondrial cristae were distorted, whereas the mitochondria were almost completely degraded in spores treated with 5.0 ppm. Meanwhile, the results from microscopy studies using laser scanning confocal microscope and fluorescence microscope showed that ozone treatment caused production of reactive oxygen species (ROS) in mitochondria of C. gloeosporioides. With increased concentration of ozone, higher levels of ROS were induced in the spores. Besides its direct antifungal activity, the study strongly suggested that ozone induces a series of defense reactions through production of compounds such as total phenols, polyphenol oxidase (PPO), peroxidase (POD) and phenylalanine ammonia-lyase (PAL) in ozone-fumigated papaya. Likewise, content of ascorbic acid, β-carotene, lycopene and antioxidant activity of papaya increased as fruit ripened and was further enhanced by exposure to ozone for 96 hours from day 4 until day 8. Twenty-four hours of ozone treatment at the level of 0.5, 2, 3.5 and 5.8 ppm reduced the total mesophilic microorganism counts of fruit with initial values of 4.48 to 2.18 log cfug-1. In addition, no coliform bacteria were initiated after 24 hours at all levels of ozone exposure. In addition, 2.5 ppm ozone treated fruit showed maximum beneficial effects in reducing weight loss, maintaining firmness, reduced rate of respiration, delaying changes in peel colour and containing the highest soluble solids concentration (SSC) as compared to the control. The titratable acidity declined throughout the storage period with slower rate in ozone-fumigated fruits. Overall sensory assessment of quality after ripening showed fruit were significantly better in quality when fumigated with 2.5 ppm ozone which were assigned highest sensory score in terms of appearance, sweetness, pulp colour, texture, aroma and overall acceptability than the control. The discovery of the gene expression of papaya in defense response induced by ozone fumigation has further clarified the understanding on how specific gene involved in controlling its expression when the plant changes during stress or in any plant lifecycle event. Among those genes, some involved in ethylene biosynthesis, generation of reactive oxygen species and stress responses of plant defense were found (mitochondrion, chloroplast, heat shock proteins, polygalacturonase-inhibiting protein, hydroxyproline-rich glycoprotein, ethylene responsive factor and acyl-CoA oxidase). Thus, the findings from all the experiments carried out during this study showed that 2.5 ppm ozone reduced anthracnose incidence and extended the storage life for up to 12 days while maintaining acceptable quality of papaya fruit. Ozone exposure at 1.5 ppm resulted in poorer quality fruit as compared to 2.5 ppm ozone treated fruit. Higher concentration of ozone exposure at 3.5 ppm and 5 ppm ozone seems non-physiological and caused phytotoxic effect on the quality of papaya fruit. As a non-toxic, biodegradable product, eco-friendly and safe sanitizer, ozone has the potential to become a natural preservative for prolonging the shelf life and retaining quality of papaya by combating fungal disease, particularly fungus C. gloeosporioides, thus promoting the marketability of the crop and minimizing postharvest losses in the papaya industry.